Glycemic Status and Renal Function among Type 2 Diabetics (Bangladesh Journal of Medical Science, 2014)
Background: Diabetes mellitus (DM) is characterized by some specific complications including diabetic nephropathy. Urea & creatinine are useful parameters to diagnose the renal function, despite some limitations. Objective: This study aimed to analyze the effect of hyperglycemic condition on the renal function parameters like serum urea and serum creatinine. Methods: It was a cross sectional study. To determine the incidence of kidney dysfunction in type 2 diabetics in Nepalgunj Medical College and Hospital, Nepalgunj, Nepal. Random blood samples were taken from 100 diabetic subjects and 100 non-diabetic controls between the period 1st February, 2012 to 31st January, 2013 for investigation of fasting plasma glucose (FPG), blood urea and serum creatinine. These biochemical parameters were determined by using a fully automated clinical chemistry analyzer. The comparison was done by using Student t test. Results: Our findings showed that the level of blood urea (P